Speech Act Analysis of Madurese Wedding Ceremony in Kalidandan Village, Pakuniran, Probolinggo - Anwari, Anwari (State institute of islamic studies salatiga, 2020)
Pragmatics is the study of those relations between language and context that are grammaticalized, or encoded in the structure of language. This study aims to describe kinds of speech acts especially locutionary act, illocutionary act, and the perlocutionary act of Madurese wedding ceremony in Kalidandan village, Pakuniran district, Probolinggo regency. The results of this study showed that the illocutionary act of the Madurese wedding ceremony in Kalidandan village, Pakuniran district, Probolinggo regency has various kinds of speech act, 1) direct speech act; 2) indirect speech act; 3) literal speech act; 4) non-literal speech act; 5) direct literal speech act; 6) indirect literal speech act; 7) direct non-literal speech act, and 8) indirect non-literal speech act.Keywords: Speech act, Kinds of speech act, and Madurese